Ptice Kozjanskega regijskega parka - Jančar, Tomaž (Acrocephalus, 2000)
In 1999, a survey of the birds of Kozjansko Regional Park (198 km2) was carried out by members of the DOPPS-BirdLife Slovenia. For this purpose, the transect method with two belts was applied. Each of the 54 transects in a total length of 58.3 km was surveyed twice. The Parkćs territory was divided in 5 landscape types, each with its characteristic combination of habitat types. Data were gathered separately for each landscape type. 120 species wereregistered on the basis of the carried out survey and the data from literature. 105 of these were breedersČ 79 confirmed, 9 probable and 17 possible breeders. 7,159 pairs were registered within the transects. The Parkćs most abundant breeders areČ Great Tit Parus major (7,300-9,300 pairs), Blackcap Sylvia atricapilla (7,200-9,200), Tree Sparrow Passer montanus (6,500-8,200), Chaffinch Fringilla coelebs (5,700-7,300), Blackbird Turdus merula (5,300-6,900), Robin Erithacus rubecula (5,000-6,500) and House SparrowPasser domesticus (5,000-6,400). Very common are the species closely associated with traditional orchards, which the Park does not lack, i.e.Č Wryneck Jynx torquilla (700-1,000 pairs), Common Redstart Phoenicurus phoenicurus (510-780), Grey-headed Woodpecker Picus canus (100-250), Green Woodpecker Picus viridis (50-150) and particularly Red-backed Shrike Lanius collurio (2,300-3,200). Very interesting from the point of nature conservationareČ Corn Crake Crex crex (7-10), Collared Flycatcher Ficedula albicollis (50-200), Corn Bunting Miliaria calandra (50-150) and Eurasian Scops Owl Otus scops (10-20). (Abstract truncated at 2000 caracters)
Keywords: Ornitologija; Ptice; bird; Kozjansko; narodni parki; naravna dediščina; Kozjanski park